PENGARUH TAKARAN PUPUK KANDANG AYAM DAN PUPUK KALIUM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata L.) VARIETAS TALENTA - Yudi Yusdian, Joko Santoso dan Elsa Gita Rudiana (Program Studi Agroteknologi Faperta UNIBBA, 2021)
This research aimed to figure out the interaction between chicken manure dosage and potassium fertilizer towards the growth and crop yields of sweet corn (Zea mays saccharata L) Varieties of Talenta and to obtain the right dosage of chicken manure and potassium fertilizer that could give the best impact towards the growth and crop yields of sweet corn (Zea mays saccharata L) Varieties of Talenta. This research had been started from March to June 2021, in Ciheulang Village, RT 02 RW 06, Ciparay District, Bandung Regency, Province of West Java, by height ±750 meters above the sea level. This research used factorial pattern Randomized Block Design method with 3 times repeat. Factor I: the dosage of chicken manure (a1 = 5 ton/ha, a2 = 10 ton/ha, a3 = 15 ton/ha). Factor II: the dosage of potassium fertilizer (k1 = 100 kg/ha, k2 = 150 kg/ha, k3 = 200 kg/ha). The result findings showed that occured interaction between the dosage of chicken manure and the dosage of potassium fertilizer towards the plant’s height at the age of 35 days after planting, it was showed by the combination of a3k3 treatment (15 ton/ha of dosage of chicken manure and 200 kg/ha of dosage of potassium fertilizer). The giving of chicken manure with dosage 15 ton/ha gave better impact towards the height of plants and cob weights without cornhusk per plot. The giving of potassium fertilizer with dosage 150 kg/ha gave better impact cob weights without cornhusk per plot. While the dosage of 200 kgs/ha of potassium fertilizer gave impact towards the height of plant.